Investigations on the Mechanical Properties of Natural Fiber Granulated Composite Using Hybrid Additive Manufacturing: A Novel Approach. (3rd May 2021) - Anandkumar, R.; Ramesh Babu, S.; Sathyamurthy, Ravishankar
Abstract : In this work, experiments on mechanical properties such as tensile, flexural, effects, and stiffness testing are performed on natural fiber granulated composites (NFGC) manufactured using a hybrid additive manufacturing technique. The natural fiber granulated composites are prepared using the powdered form of sugarcane, jute, ramie, banana, pineapple fiber, and seashell powder with a volume fraction of 0.8. In the hybrid additive manufacturing technique, the fused deposited modeling (FDM) machine is modified by combining with the shape deposition modeling (SDM) to print the specimens layer by layer, and the influence of the number of layers on the mechanical properties is analyzed. The results concluded that increasing the number of layers from 6 to 12 improved the mechanical properties such as tensile strength, flexural strength, impact strength, and hardness values by 40.84, 50.04, 21.55, and 20.55%, respectively. Further, a novel technique can be utilized for developing the composites in replacement with conventional methods.